TELEKOM Malaysia: Malaysia\'s Leading Telecommunication Company - Innovating The Business In The Highly Competitive Market - Wan Mohamad, Wan Murdani (2011)
TM historically started its operations in1946 as a Telecommunication Department, which was then detached from Government through corporatization in 1987. It was later privatized and publicly listed in 1990. It assumed the name of Telekom Malaysia Berhad (TMB) and was subsequently known as TM, pursuant to a major corporate rebranding exercise in 1995. TM evolved to become the largest integrated telecommunication company in Malaysia and one of the leading telecommunication companies in the region. As an integrated telecommunication service provider, TM was governed by a set of corporate values; total commitment to customers, uncompromising integrity and respects and care, which were manifested in the management practices, company policies, business operations, products offerings and corporate services. At as pinnacle, TM recorded the operating revenue of RM17.8 billion with staggering market capitalization of RM38.5 billion as well as presence in more than 12 countries within the Asian region.